In-Silico Prediction of Common siRNA Targeting Protein Coding Sequence of NS5 Gene of West Nile and Japanese Encephalitis Virus : siRNAs against West Nile and Japanese Encephalitis viruses - Islam, Rahatul; Shahriar, Asif; Siddiquee, Mohd. Faijanur-Rob; Fatema, Nour; Uddin, Muhammad Ramiz; Acharjee, Mrityunjoy; Aurin, Khosnur Jahan; Shepon, Md Mukhlesur Rahman; Bhuiyan, Ashikur Rahaman; Gomesh , Marline (Trends in Peptide and Protein Sciences, 2023)
West Nile virus (WNV) and Japanese Encephalitis virus (JEV) are two major mosquito-borne flaviviruses that share almost similar symptoms after infection, e.g., flu-like symptoms. Though JEV is the most common cause of encephalitis (brain inflammation), recent studies have discovered approximately 30% involvement of the WNV in this. Furthermore, both viruses share similar genetic constituents with more than 70% homology. Therefore, these two viruses sometimes cause misdiagnosis due to their co-circulation with the same vector, and no solid protective treatment has yet been discovered against them. As a result, in this study, we used small interfering RNAs to provide dual protection against both viruses. The siRNAs have high demand as a potential treatment option for genetic treatments, and antiviral or antibacterial therapeutics for many diseases. In this study, we concluded that a single highly potent siRNA (5'-UCUCUUUCCCAUCAUGUUGUA-3') could be effective in silencing the coding sequences (CDS) of both WNV and JEV by utilizing several computational assays such as GC content, free energy of binding, free energy of folding, melting temperature, siRNA efficacy prediction, and molecular docking. After structural analysis (molecular modeling and docking), we found that this siRNA effectively binds with the human Argonaute-2 (AGO2) protein. Consequently, this siRNA could be a potential therapeutic development target against both viruses by silencing the CDS. Our research aims to develop genome-level therapies. The results can be applied to develop RNA molecules as a drug against WNV and JEV. HIGHLIGHTS Promising siRNA target identified for dual protection against WNV and JEV. Efficient siRNA molecule S2 shows high binding affinity with human AGO2 protein. siRNA targeting NS5 gene shows promise for treating WNV and JEV-mediated infections.